Private low cost housing: Implication towards consumers - Syed Ibrahim, Sharifah Sofiah 'Atiqah; Jamaluddin, Zakiyah; Abu Yazid, Afifah (Institut Kajian Pengguna, Universiti Utara Malaysia, 2001)
The objectives of low cost housing construction are to help the poor and eradicate poverty as it is parallel with the New Economic Policy. Thus, the developer has to consider the provision of low cost house and the economic cost to the target group which at the same time not to reduce the quality of the houses. The research carried out in one of the private low cost housing in Jitra, Kedah revealed that most of the consumers are not satisfied with the physical structure, cooking area (kitchen space), the quality of the construction material, the quality of drainage system and maintenance system. At the same time the interior structure and house design frustrates the occupants thus forcing them to extent the house or renovates the whole structure itself. Dissatisfaction among consumers are also found in aspects of garbage collection, playground, maintenance and cleaning services, local stores, local praying area such as " surau" and parking space.